Respuesta :

[tex]\huge{\color{red}{\fbox{\textsf{\textbf{Answer}}}}} [/tex]

When an expression can be viewed as the difference of two perfect squares, i.e. a²-b², then we can factor it as (a+b)(a-b). For example, x²-25 can be factored as (x+5)(x-5). This method is based on the pattern (a+b)(a-b)=a²-b², which can be verified by expanding the parentheses in (a+b)(a-b).

[tex]100 {}^{2} - 99 {}^{2} = (100 - 99)(100 + 99)[/tex]

[tex]100 {}^{2} - 99 {}^{2} = 199[/tex]

We can establish the relation:

[tex]x {}^{2} - y {}^{2} = (x - y)(x + y)[/tex]

or vice versa.

[tex](x - 2)(x + 2) = x {}^{2} - 4[/tex]

[tex]4x {}^{2} - 49 = (2x - 7)(2x + 7)[/tex]

ACCESS MORE
EDU ACCESS